Water adsorption behavior of Mg and Fe substituted microporous AlPO4-5. (October 2022) - Dawaymeh, Fadi; Gaber, Dina Ali; Gaber, Safa Ali; Reddy, K. Suresh Kumar; Basina, Georgia; Ismail, Issam; Subrati, Ahmed; Ismail, Ola; Karanikolos, Georgios N.; Al Wahedi, Yasser F.
Abstract: Isomorphic substitution of zeolite and zeotype materials plays a dominant role in tuning the performance of the materials in adsorption and catalysis. Here, aluminophosphate AlPO4 -5 crystals (AFI-type) with variable content of incorporated iron or magnesium were hydrothermally synthesized, characterized, and tested for water adsorption. The metal incorporation altered the growth direction and thus morphology of the resulting crystals, while the Al/P ratio decreased below unity with increasing Fe/Al2 O3 or Mg/Al2 O3, confirming selective substitution of aluminum. Moreover, the unit cell experienced shrinkage when Fe substituted Al, whereas the MgAPO-5 lattice refinement results revealed minor variation in the lattice parameters. Water vapor adsorption studies revealed that the materials exhibit non-typical, type-V adsorption behavior with initial low uptake, indicating hydrophobicity, followed by a steep capacity increase indicating capillary-like adsorption at higher relative pressures. Metal substitution could tune the behavior, i.e. by increasing hydrophilicity at the lower range of relative pressures, with the onset of the inflection point being shifted to lower P/P 0 values with increasing metal content. An Fe-based AlPO4 -5 yielded the highest absorption capacity among all adsorbents tested (13 mmol/g at 43 °C). Fowler-Guggenheim calculations showed that the interaction energy ( ω ) between the adsorbed water molecules was positive for both MgAPO-5 and FeAPO-5 indicating attractive intermolecular interactions, yet a decrease of ω with increasing Me/Al2 O3 ratio in the synthesis mixture revealed suppression of intermolecular interactions with metal loading. The reported results and the tailoring of water adsorption behavior by metal substitution can be promising for water sorption/separation applications such as atmospheric water harvesting. Graphical abstract: Unlabelled Image Highlights: The effect of metal substitution on the water adsorption behavior of AlPO4 -5 is evaluated. Al/P ratio below unity confirms selective substitution of aluminum. Metal incorporation affects the position of the inflation point of the S-type isotherms and the maximum water uptake. Decrease of interaction energy ( ω ) with increasing Me/Al2 O3 ratio reveals a decrease in water intermolecular interactions with metal loading. A Fe-based AlPO4 -5 yielded the highest absorption capacity of 13 mmol/g at 43 °C.